Lipofilling after Laser-Assisted Treatment for Facial Filler Complication: Volumetric and Regenerative Effect. Issue 3 (23rd February 2021) - De Santis, Giorgio; Pinelli, Massimo; Benanti, Elisa; Baccarani, Alessio; Starnoni, Marta
Abstract : Background: Nonresorbable substances are still injected to enhance soft-tissue volumes and fill subcutaneous defects. The minimally invasive intralesional laser treatment can remove foreign substances and the inflammatory reaction, eventually leaving depression and scar tissue in the treated area. Fat grafting can restore volume loss and improve scar tissue. Methods: From March of 2010 to February of 2017, 33 patients were studied. All of them had suffered from inflammatory reactions to permanent facial fillers and had been treated with the 808-nm diode laser at the authors' institution. The evacuation of material had left facial asymmetry and visible depression. To restore facial aesthetic units, fat grafting was performed. The minimum follow-up was 6 months. Results: Volume restoration was recognized (according to the Global Aesthetic Improvement Scale) as significantly improved in 22 patients, moderately improved in eight patients, and slightly improved in three patients. Improvement in atrophic and scarred tissues (with an apparent thickening of the skin or even elimination of scars) was also assessed with the following results: 25 patients were very much improved and eight were moderately improved. Conclusions: This is the first study on filler-induced complications of the face treated by intralesional laser treatment followed by lipofilling. A systematic approach to volume restoration is proposed to patients who had filler removal of the face. There was a high degree of patient satisfaction with this technique. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.